MODELS OF STATE YOUTH EMPLOYMENT POLICY IN UKRAINE AND POLAND: COMPARATIVE ANALYSIS - Bondarenko, D. (Pressing Problems of Public Administration, 2019)
Reforms in Ukraine, in particular in the sphere of state policy, and globalization challenges stipulate the necessity for forming and developing a competitive model of the state policy of youth employment. This explains a growing interest in the international experience of forming models of the state youth employment policy. A study of the current Polish practices is considered to be useful, as Poland is a member state of the European Union; moreover, the country’s problems are similar to those of Ukraine, specifically – youth labor migration to advanced countries. The youth employment policy of Poland presents a system of regulatory measures and actions of socio-economic, legal, administrative and organizational nature, which are taken by public authorities and civil society institutions. It is focused on job placement of the youth, including at the regional labor market, with the aim of providing full employment of the young people. It appears that Poland tends to apply a model of state youth employment policy that can be described as paternalistic with decentralization elements. According to the Polish model, the state youth employment policy presupposes a moderate interference of the state with the life and affairs of the young generation. Also, the state contributes to effective involvement of young people in various forms of participation in the life of society and independent solution of their own problems. The Ukrainian model of the state youth employment policy is more centralized. This model is characterized by a misbalance of work force demand and supply, disagreement between employers’ requirements to young specialists and the standards and quality of their education, aggravating the tension felt in the national and regional labor markets of Ukraine. A comparative analysis of the models of the state youth employment policies in Ukraine and Poland has allowed us to identify certain compliance of the state policies of youth employment pertaining to provision of state support for those young persons who need it most. Another similarity is that the young people are getting involved in solution of their own problems by developing their active civic stand. Both in Poland and in Ukraine, the following trend is observed: the number of the unemployed is reduced (from 2013 and 2018, respectively). However in Ukraine, the highest rate of unemployment is traced among young people, and namely: at the age of 15-24 (15.6 %), 25-29 years of age (8.8 %), 30-34 y.o.a. (7.6 %). It is proposed to apply in Ukraine the European experience of implementing the state youth employment policy, using the elements of the Polish model as an example: coordination of the efforts of the local bodies of power, employers, NGOs at the regional level. The prospective scientific surveys are supposed to be research of the models of the state youth employment policy of the advanced European countries for the purpose of adapting them to the reality of Ukraine.